Pneumococcal Polysaccharide Conjugated Vaccines and the Problem of Changing Circulating Serotypes of Pneumococcus - N. N. Kostyukova; V. A. Bekhalo (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. In 2007, WHO recommended pneumococcal conjugate vaccines (PCV) be included in national immunization schedules for young children. By 2020, 145 countries, including Russia, were using PCV. Aims. To identify vaccines with high epidemiological and immunological efficacy against various forms of pneumococcal infection, including carriage. Conclusions. It has been shown that PCV has high epidemiological and immunological efficacy against various forms of pneumococcal infection, including carriage. It was revealed that the mass use of PCV, leading to the elimination of "vaccine" serotypes, is simultaneously accompanied by the spread of cases of infection due to serotypes not included in vaccines, which significantly reduces the positive effect of vaccination. This requires frequent replacement of serotype polysaccharides in the vaccine in accordance with the serotypes of circulating strains. An alternative to PCV can be vaccines based on pneumolysin, surface pneumococcal proteins, whole – cell and live attenuated, protein-based subunit vaccines, etc. vaccine variants.